A Distinctive Learning Innovation to Grasp English Grammar by Using “Make a Wish (Birthday Song)” Song by NCT U in Magnificent Way - Ikrar Genidal Riadil; Lutvi Abdullah (Universitas Teuku Umar, 2022)
Learning English by using song is one of the most enjoyable and entertaining ways that has been substituted into the school syllabus at Junior High School and Senior High School for the 2013 curriculum. The goal of this research is to approach and reinforce or affirm grammar by using NCT U’s song entitled Make a Wish (Birthday Song) by analyzing the terms of grammar from its lyrics. The goal of the study is to seek the answer two research questions: (1) What are the types of grammar structure in NCT U’s song entitled “Make a Wish (Birthday Song)”? (2) What is student’s perspectives towards using of English songs in learning grammar? This research uses a qualitative research method. The study's data is being collected from the students in Senior High School. 76% of the students agreed that using song lyrics entitled Make a Wish (Birthday Song) by NCT U is engaging lessons with the model song will motivate students to learn grammar interestingly. The researcher concludes that the terms of grammar in NCT U 's song are of a different kind, and that it is interesting to learn. Therefore, using song lyrics as a creative function to inspire students' grammar skills and motivate them to study grammar is a really fun way to know. In a nutshell, the researcher recommends using the lyrics of a song to learn grammatical tenses.